2019
DOI: 10.1016/j.cgh.2019.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Therapeutic Drug Monitoring of Biologic Agents for Patients With Inflammatory Bowel Diseases

Abstract: BACKGROUND & AIMS: Therapeutic drug monitoring (TDM) is widely available for biologic therapies in patients with inflammatory bowel disease (IBD). We reviewed current data and provided expert opinion regarding the clinical utility of TDM for biologic therapies in IBD. METHODS: We used a modified Delphi method to establish consensus. A comprehensive literature review was performed regarding the use of TDM of biologic therapy in IBD and presented to international IBD specialists. Subsequently, 28 statements on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
262
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 255 publications
(274 citation statements)
references
References 136 publications
8
262
1
3
Order By: Relevance
“…Therapeutic drug monitoring (TDM) has been recognised as an important strategy to inform clinical decision‐making in patients with inflammatory bowel diseases (IBD) . The rationale for TDM is that a systematic and algorithmic assessment of drug concentration and anti‐drug antibodies may help objectively evaluate potential reasons for failure of therapy and define next steps in management, and proactively provide opportunities for optimising therapy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therapeutic drug monitoring (TDM) has been recognised as an important strategy to inform clinical decision‐making in patients with inflammatory bowel diseases (IBD) . The rationale for TDM is that a systematic and algorithmic assessment of drug concentration and anti‐drug antibodies may help objectively evaluate potential reasons for failure of therapy and define next steps in management, and proactively provide opportunities for optimising therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The recent American Gastroenterological Association guidelines and the Sydney IBD Consensus statements on TDM focused only on TNFα antagonists . The BRIDGe group recommended use of TDM in vedolizumab‐treated patients with primary nonresponse or secondary loss of response, primarily to determine the presence or absence of drug, but could not recommend optimal trough concentrations …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TDM in biologic therapy refers to the evaluation of trough drug concentration and anti-drug antibody to help optimize the dosage regimen or select the right agents. Previous studies have shown positive correlations between drug concentrations and good clinical or laboratory outcomes, whereas low or undetectable drug concentrations can lead to immunogenicity and treatment failure [4,5]. Loss of response is currently the major problem encountered in anti-tumor necrosis factor therapy.…”
mentioning
confidence: 99%